Strategi DKM Masjid Raya PT. Dirgantara Indonesia dalam Optimalisasi Kegiatan Keagamaan - Hartati, Ida; Anwar, Saeful; Marfuah, Luk-luk Atin (Tadbir: Jurnal Manajemen Dakwah, 2021)
This study aims to determine how the planning strategy, organizing strategy, and evaluation strategy of the DKM Habiburrahman in optimizing religious activities. The research method used is descriptive method with a qualitative approach. In collecting data, it is done by using observation techniques and interviews. Based on the results of research, the DKM strategy in optimizing religious activities, namely in the planning strategy, is implemented by making a work plan called GBHP. The organizing strategy adopted was to involve PTDI employees to become DKM. Then the evaluation strategy that is applied is to carry out routine evaluation meetings to determine the work program of implementing the strategy applied. In this study, DKM strategy in optimizing religious activities was successfully implemented.